Analisis Rasionalitas Obat Antihipertensi Pada Pasien Dewasa Hipertensi Yang Menjalani Rawat Inap Di Bangsal RSUD Dr Moewardi Surakarta - Evika Risa Antasya (JURNAL ILMIAH FARMASI SIMPLISIA, 2024)
Hypertension is a circulatory disorder that causes blood pressure to rise above normal, namely ≥140/90 mmHg. The number of people with hypertension continues to increase from year to year, where it is estimated that 1.5 billion people will be affected by hypertension in 2025 and 10.44 million people will die every year due to hypertension and its complications. Irrational drug use is a global problem that endangers public health. This study aims to determine rationality analysis of antihypertensive drug in adult hypertension patients undergoing inpatient in RSUD Dr. Moewardi Surakarta period January-December year 2022. This research is an observational descriptive study with cross sectional method that retrieves data retrospectively from medical records patient. Rationality analysis was performed using the 8T method. Population that used in this study were adult hypertensive patients undergoing inpatient at in RSUD Dr. Moewardi Surakarta period January-December year 2022, with a total sample of 100 samples. The results obtained are right diagnosis (100%), right indication (100%), right drug selection (99%), right dose (92%), right way of giving the drug (100%), right time interval of administration (94%), appropriate long gift (100%), and right assessment patient's condition (100%).